Targeting assessment in the primary classroom : strategies for planning, assessment, pupil feedback and target setting - Clarke, Shirley. (Hodder and Stoughton, 1998)
This book is about: Planning; Sharing learning intentions with children; Making and feedback; Target setting; ...